Verde dice adelante - Ring, Susan (Mankato, MN : Capstone Press, 2006)
"Simple text and photos introduce basic traffic rules"
Rojo dice alto -- Verde dice adelante -- Amarillo dice cuidado -- Tengo cuidado en mi bicicleta -- Tengo cuidado cuando juego -- Tengo cuidado cuando pasa el tren -- Tengo cuidado cada día.
Includes index.
Keywords: Traffic signs and signals -- Juvenile literature; Traffic signs and signals; Spanish language materials -- Bilingual